2020
DOI: 10.3390/ijerph17176132
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Absenteeism: The Role of Workplace and Non-Workplace Stressors

Abstract: Unplanned absenteeism (UA), which includes medically certified leave (MC) or emergency leave (EL), among nurses may disturb the work performance of their team and disrupt the quality of patient care. Currently, there is limited study in Malaysia that examines the role of stressors in determining absenteeism among nurses. Therefore, apart from estimating the prevalence and the reasons of UA among nurses in Malaysia, this study aims to determine its stressor-related determinants. A cross-sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
1
7
0
1
Order By: Relevance
“…Appointments within 48 hours, convenient health care access comparable to private practice, and flexibility could all contribute considerably to patient satisfaction and acceptance of the Consult Station health care system, as reported with other telemedicine devices [ 32 , 33 ]. Furthermore, the system could help limit absenteeism from work due to illness if booths are implemented in the workplace as in our study [ 34 , 35 ]. In a recent study, the authors found that the rate of absenteeism from work was 3% among 5465 employees, with 56% of absences from women [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appointments within 48 hours, convenient health care access comparable to private practice, and flexibility could all contribute considerably to patient satisfaction and acceptance of the Consult Station health care system, as reported with other telemedicine devices [ 32 , 33 ]. Furthermore, the system could help limit absenteeism from work due to illness if booths are implemented in the workplace as in our study [ 34 , 35 ]. In a recent study, the authors found that the rate of absenteeism from work was 3% among 5465 employees, with 56% of absences from women [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absenteeism was the main outcome defined by four questions: “Within the past 6 months, have you been absent from your job?”, “How often have you been absent in the last 6 months?”, “What were the reasons you were absent from work in the last 6 months?”, and “If the main reason was due to own illness, was it due to COVID-19?”. Aligned with previous studies on absenteeism, reasons for absenteeism were classified into planned or unplanned ( 23 , 27 ). Planned absenteeism was defined as voluntary planned leave, such as annual leave, vacation, study leave, or maternity/paternity leave; whereas unplanned absenteeism was due to involuntary circumstances, such as emergency leave, short-term self-certified sickness absence, medically certified sickness, taking care of a family member, and other family responsibilities ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we considered absenteeism the habitual non-presence of an employee at their job that is not formally justified to the employer or linked to the illness. Usually, it takes just a couple of days but may be more frequent 21 22…”
Section: Methodsmentioning
confidence: 99%